Implementation of Research, Planning, Implementation, Evaluation (RPIE) in Developing Publish Awareness Through Instagram by Public Relations of Hope Worldwide Indonesia - Stefanny, Jovanca; Muhammad Athalarik, Fadli; Astuti, Hani; Imaddudin, Imaddudin (Siber Journal of Advanced Multidisciplinary, 2024)
This research was conducted to determine the implementation of the RPIE concept in the role of PR to develop public awareness through Instagram of the HOPE Worldwide Indonesia organization. This research uses a type of qualitative research with descriptive research methods. The results of the study show that the role of PR in developing public awareness through the use of Instagram is carried out in several steps, namely 1) research, namely finding out the target audience with insight and research features used for making posts using SDG-type hashtags and seeing existing trends, 2) planning, namely PR having SOP, having a workflow in creating content and using digital media to develop wider public awareness, 3) implementation, namely public relations using the Instagram platform and activating all of its features, having a different core message from each content that is relatable, applying SOP in postings to packaging the content properly, 4) evaluation, namely PR HOPE Worldwide Indonesia conducted a review of the performance they had carried out to raise public awareness, look for data by looking at Instagram insights, seeing and feeling the changes and impacts that had occurred. The limitation of this research is that this research is only limited to how to implement the RPIE concept in the Instagram of HOPE Worldwide Indonesia. The Practical Implications of this research can provide benefits for researchers to explain the role played by a public relations person in developing public awareness of non-profit organizations through Instagram. The originality of this research is This research discusses HOPE Worldwide Indonesia as a non-profit organization that operates Instagram as one of its organizational media.